A Survey on the Legal Requirements of Local Content Utilization in the Upstream Petroleum Industry - Seyed Nasrollah Ebrahimi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2018)
Recently, the resource-rich countries by adopting a variety of policies has intended to increase their shares in petroleum operations. The law enactment as to the requirement for local content utilization is a way through employing the workforces, equipment and products locally provided in the territory by increasing the value-added to the country’s economic other than the extraction project. Upon oil exploration in Iran, especially after the nationalization of petroleum industry and also the Islamic revolution, different rules and regulations have been enacted in respect of local content. Currently, the “Law on Maximum Utilization of Manufacturing and Service Rendering Capabilities to Resolve the Country’s Requirements and Strengthen them in the Course of Export and to Modify the Article (104) of Direct Tax Act” is the most important instrument which reflects the local content requirements including: project assignment to Iranian companies, Iranian-foreign joint venture or foreign companies, performance requirement, respecting minimum percentage (51%), information requirement, monitoring and controlling requirement and refers to the sanctions of defaults and exceptions. This article attempts to explain each of the mentioned requirements, sanctions and exceptions and refers to the existing gaps by considering the characteristics of petroleum industry and proposes respective recommendations as to the case.